Futurization of Aging: Subjective Beliefs and Effects - Olga Strizhitskaya; Marina Petrash; Daria Golubitskaya; Maria Kuzmina; Kristina Krupina; Anton Shchukin; Elena Engelgardt (Behavioral Sciences, 2022)
Aging in the face of an increasing population and growing life expectancy is considered one of the major demographic challenges in modern society. Previous research has revealed that quality of life in aging could significantly differ depending on the resources one possesses. However, little attention has been given to the mechanisms of formation of these resources and the role of intentionality. In the present study, we identified 22 strategies that favor a better life quality in aging and analyzed them from the perspective of subjective beliefs and reported performance. Our sample was adults (n = 72) aged 57–65, living in St. Petersburg, Russia. The results showed that although participants were aware of the strategies that favor aging, their reported performance ranged on a scale from average to infrequent use of these strategies. We found that subjective beliefs about the role of psychological resources for better aging predicted higher scores on subjective beliefs about the role of lifestyle resources and the reported performance of psychological resources. Our results suggest that there is a gap between subjective beliefs about the controllability of aging processes and the transformation of these beliefs into real performance.